Method for producing iota-alumina and iota-alumina
By heating and cleaning the solid raw materials of alkali metal compounds, fluorides and aluminum compounds under low temperature conditions, the problems of high temperature and complex processes in the prior art are solved, and an efficient and simplified method of ι-alumina production is realized.
Patent Information
- Application Number
- CN202380057156.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-02
- Filing Date
- 2023-08-01
- Publication Date
- 2025-03-18
AI Technical Summary
The process for manufacturing ι-alumina in the prior art requires high temperature and complex processes, and the equipment requires high temperature tolerance and gas exchange capability.
By adopting a low temperature and simple process, a solid raw material of alkali metal compound, fluoride and aluminum compound is heated and washed in a polar solvent, a rod-shaped or needle-shaped alumina crystal is generated.
It realizes efficient manufacturing of ι-alumina under low temperature conditions, simplifies the process, reduces equipment requirements, and obtains high-purity ι-alumina crystals.
Smart Images

Figure CN119654294A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing iota-alumina and iota-alumina. Background Art
[0002] In the prior art, as a method for producing iota-alumina, it is necessary to mix aluminum oxynitride and carboxymethyl cellulose, for example, and heat them to 1000°C or above by a sol-gel method, and thus an apparatus capable of withstanding high temperatures is required (Non-Patent Document 1). In addition, Patent Document 1 discloses a method for producing flat iota-alumina by oxidizing a molten alkali metal haloaluminate with oxygen or an oxygen-containing gas at a temperature of 400°C to 800°C (Patent Document 1). However, it is necessary to introduce an oxygen-containing gas into the melt during the heating process, and thus it is necessary to use a reaction apparatus capable of performing gas exchange during the heating process.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 05-201723
[0006] Non-patent literature
[0007] Non-patent literature 1: Mullite-type Na0.67Al6O9.33 and a discussion of iota-alumina, Journal of the European Ceramic Society 40 (2020) 4276-4280. Summary of the invention
[0008] Problems to be solved by the invention
[0009] The present invention provides a method for producing iota-alumina at a low temperature and in a simple process, and iota-alumina having a rod-like or needle-like crystal habit obtained by the above production method.
[0010] Technical solutions to solve problems
[0011] The first method for producing iota-alumina is characterized by comprising: a reaction step of mixing and heat-treating a solid raw material comprising an alkali metal compound, a fluoride and at least one material selected from an aluminum compound and aluminum; and a washing step of placing the product generated by the above reaction step into a polar solvent.
[0012] In the first embodiment, the alkali metal compound may be at least one selected from sodium aluminate (NaAlO2), sodium borates, sodium hydride (NaH), sodium borohydride (NaBH4) and sodium oxide (Na2O), and potassium aluminate (KAlO2), potassium borates, potassium hydride (KH), potassium borohydride (KBH4) and potassium oxide (K2O).
[0013] In the first aspect, the sodium borates may be at least one selected from the group consisting of sodium metaborate (NaBO2), sodium tetraborate (Na2B4O7) and sodium diborate (Na4B2O5).
[0014] In the first embodiment, the potassium borates may be at least one selected from potassium metaborate (KBO2), potassium tetraborate (K2B4O7) and potassium diborate (K4B2O5).
[0015] In the first embodiment, the fluoride may be at least one selected from sodium fluoride (NaF), sodium hexafluoroaluminate (Na3AlF6), potassium fluoride (KF), potassium fluoroaluminate (KAlF4), potassium hexafluoroaluminate (K3AlF6), aluminum fluoride (AlF3) and lithium fluoride (LiF).
[0016] In the first embodiment, the aluminum compound may be at least one selected from the group consisting of sodium aluminate (NaAlO 2 ), potassium aluminate (KAlO 2 ), aluminum oxide (Al 2 O 3 ) and aluminum fluoride.
[0017] In the first embodiment, the polar solvent may be water.
[0018] In the first embodiment, the polar solvent is water, and the product and the water may be stirred at 80° C. or higher and 100° C. or lower in the washing step.
[0019] The crystal habit of the iota-alumina crystals of the first embodiment is rod-like, needle-like, or flat-plate-like.
[0020] In the first aspect, the average aspect ratio of the iota-alumina crystals may be 3 or more and 30 or less.
[0021] In the first embodiment, the iota-alumina crystals have a rod-like or needle-like crystalline habit and may contain sodium.
[0022] In the first embodiment, the iota-alumina crystals have a rod-like or plate-like crystalline habit and may contain potassium.
[0023] Effects of the Invention
[0024] According to the first aspect, it is possible to provide a method for producing iota-alumina at a low temperature and in a simple process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1A This is a SEM (Scanning Electron Microscope) reflected electron image of a cross section of a bulk reaction product that was stirred with water at 80° C. to 100° C. for 1 hour and then washed.
[0026] Figure 1B yes Figure 1A An enlarged SEM reflection electron image of the range IB is shown.
[0027] Figure 1C It is observation Figure 1A An enlarged SEM reflection electron image of iota-alumina crystals obtained by observing the surface of the product involved.
[0028] Figure 1D is different from Figure 1C Observation of the parts Figure 1A An enlarged SEM reflection electron image of iota-alumina crystals obtained by observing the surface of the product involved.
[0029] Figure 1E Yes means Figure 1C An enlarged SEM reflection electron image of iota-alumina crystals with measured aspect ratios for range IE shown.
[0030] Figure 1F Yes means Figure 1D An enlarged SEM reflection electron image of the iota-alumina crystals with measured aspect ratios in the range IF shown.
[0031] Figure 1G This is an enlarged SEM reflection electron image of iota-alumina crystals involved in the product obtained using potassium metaborate (KBO2) as the alkali metal compound.
[0032] Figure 1H This is an enlarged SEM reflection electron image of iota-alumina crystals involved in the product obtained using potassium metaborate (KBO2) as the alkali metal compound.
[0033] Figure 2 This is a SEM reflection electron image of powdered iota-alumina crystals obtained by high-temperature washing the reaction product with boiling water.
[0034] Figure 3 1 is a process diagram showing a first method for producing iota-alumina.
[0035] Figure 4 1 is a process diagram showing a second method for producing iota-alumina.
[0036] Figure 5This is a process diagram showing a third method for producing iota-alumina.
[0037] Figure 6 This is a process diagram showing a fourth method for producing iota-alumina.
[0038] Figure 7 This is a partial cross-sectional view showing an example of a closed container used in the first to fourth manufacturing methods.
[0039] Figure 8 This is a partial cross-sectional view showing another example of the closed container used in the first to fourth manufacturing methods.
[0040] Fig. 9 This is a partial cross-sectional view showing another example of the closed container used in the first to fourth manufacturing methods.
[0041] Fig.10 This is a partial cross-sectional view showing still another example of the closed container used in the first to fourth manufacturing methods.
[0042] Fig.11A is used Figure 8 The sealed container 10B shown is a front view of the appearance of a stirrer having a plate-shaped (blade) stirrer.
[0043] Fig. 11B is used Figure 8 The sealed container 10B shown is a side view photograph of the appearance of a stirrer having a plate-shaped (blade) stirrer.
[0044] Fig. 12A is used Figure 8 The photograph of the closed container and the blade stirring bar after the reaction product is taken out of the container after the stirring for a predetermined time is shown.
[0045] Fig. 12B is used Figure 8 The closed container shown is a photograph of the reaction product after it has been stirred for a predetermined period of time and then removed from the container.
[0046] Fig.13A Yes Fig.10 A photograph of a closed vessel before the horizontal wide paddle (WP) stirring bar is rotated to produce iota-alumina.
[0047] Fig. 13B Yes Fig.10 A photograph of a closed container after production of iota-alumina with a horizontal wide paddle (WP) stirring bar rotating is shown.
[0048] Fig.14A Schematic diagram showing the reaction of forming iota-alumina.
[0049] Fig. 14B Schematic diagram showing the reaction of forming iota-alumina.
[0050] Fig. 14C Schematic diagram showing the reaction of forming iota-alumina.
[0051] Fig.14D Schematic diagram showing the reaction of forming iota-alumina.
[0052] Fig.14E Schematic diagram showing the reaction of forming iota-alumina.
[0053] Fig.14F Schematic diagram showing the reaction of forming iota-alumina.
[0054] Fig.15 This is a diagram showing the X-ray diffraction pattern of the product according to Test Example 1.
[0055] Fig.16 This is a diagram showing the X-ray diffraction pattern of the product according to Test Example 3.
[0056] Fig.17 This is a diagram showing the X-ray diffraction pattern of the product according to Test Example 4.
[0057] Fig.18 This is a diagram showing the X-ray diffraction pattern of the product involved in Test Example 6.
[0058] Fig.19 This is a diagram showing the X-ray diffraction pattern of the product involved in Test Example 7.
[0059] Fig. 20 This is a diagram showing the X-ray diffraction pattern of the product involved in Test Example 8.
[0060] Fig.21 This is a diagram showing the X-ray diffraction pattern of the product involved in Test Example 18.
[0061] Fig. 22 This is a diagram showing the X-ray diffraction pattern of the product involved in Test Example 24. DETAILED DESCRIPTION
[0062] The following describes the embodiments of the present invention with reference to the accompanying drawings, but the present invention is not limited thereto. The constituent elements of the embodiments described below can be appropriately combined. Moreover, some constituent elements may not be used sometimes. In addition, the constituent elements in the embodiments described below include elements that can be easily thought of by a person skilled in the art, are substantially the same, and are within the so-called equivalent range.
[0063] The iota-alumina (Iota-alumina: Na 0.67 Al6O 9.33 or K 0.67 Al6O 9.33 ) has a reaction step and an extraction step.
[0064] The reaction step is a step of heating the solid raw materials.
[0065] The solid raw material includes an alkali metal compound, a fluoride, and at least one material selected from an aluminum compound and aluminum.
[0066] As the raw material alkali metal compound, at least one selected from sodium aluminate (NaAlO2), sodium borates, sodium hydride (NaH), sodium borohydride (NaBH4) and sodium oxide (Na2O), and potassium aluminate (KAlO2), potassium borates, potassium hydride (KH), potassium borohydride (KBH4) and potassium oxide (K2O) can be used.
[0067] Specific examples of raw sodium borates include borax (sodium tetraborate: Na2B4O7), sodium metaborate (NaBO2 (=Na2B2O4)), sodium diborate (Na4B2O5), potassium metaborate (KBO2 (=K3(B3O6))), potassium tetraborate (K2B4O7) and sodium diborate (K4B2O5) or a combination of at least two or more thereof, but are not limited to these.
[0068] When sodium metaborate is used as the sodium borate, powdered sodium metaborate powder (sodium metaborate powder) can be used. The particle size of the sodium metaborate powder is preferably less than 100 μm. The sodium metaborate powder is obtained by passing through a sieve with a mesh of 100 μm after being finely crushed to a certain extent. When the particle size of the sodium metaborate powder exceeds 100 μm, the generation efficiency of sodium borohydride may be reduced. The particle size of the sodium metaborate powder is more preferably less than 100 μm. That is, the sodium metaborate powder is preferably obtained by passing through a sieve with a mesh size less than 100 μm (for example, a sieve with a mesh size of less than 50 μm, etc.). At this time, the generation efficiency of ι-alumina can be further improved.
[0069] Since the sodium metaborate powder contains water, the amount of the sodium metaborate powder is preferably larger than the amount required for synthesizing sodium borohydride by the mass of the water.
[0070] Examples of the raw material potassium borates include potassium metaborate (KBO2), potassium tetraborate (K2B4O7) and potassium diborate (K4B2O5) or a combination of at least two or more thereof, but are not limited thereto.
[0071] As raw aluminum, powder materials, scrap materials, etc. can be used. For example, aluminum chips can be scrap materials such as cutting powder and scraps. It is preferable that the aluminum chips contain as little as possible a metal nobler than aluminum as an impurity.
[0072] The amount of aluminum is preferably set to be 110% or more of the amount required for synthesizing sodium borohydride in terms of molar ratio. A portion of the remaining aluminum is consumed by reaction with water, and when the amount of aluminum as a raw material decreases as the reaction proceeds, it also helps to increase the chance of contact with sodium metaborate, thereby improving the yield. In addition, the excess aluminum can be recovered and reused as aluminum metal in the washing process of sodium borohydride.
[0073] The average particle size of the aluminum powder is, for example, 1 μm or more, and the maximum particle size is preferably 10 mm or less. When the average particle size of the aluminum powder is less than 1 μm, dust explosion is likely to occur, resulting in difficulty in handling, and sometimes particles are likely to adhere to each other and consolidate with each other. When the average particle size is greater than 10 mm, the specific surface area per unit mass decreases, and sometimes the reaction area decreases, resulting in an extreme decrease in the initial reaction rate. The average particle size of the aluminum powder is more preferably 5 μm or more and 5 mm or less. The average particle size is obtained as the particle size of a sphere equivalent diameter using a laser diffraction particle size distribution measuring device.
[0074] As the raw material aluminum compound, at least one selected from sodium aluminate (NaAlO 2 ), potassium aluminate (KAlO 2 ), aluminum oxide (Al 2 O 3 ) and aluminum fluoride (AlF 3 ) can be used.
[0075] The raw material fluoride is at least one selected from sodium fluoride (NaF), sodium hexafluoroaluminate (Na3AlF6), potassium fluoride (KF), potassium fluoroaluminate (KAlF4), potassium hexafluoroaluminate (K3AlF6), aluminum fluoride (AlF3) and lithium fluoride (LiF). Among them, sodium fluoride as an alkali metal fluoride is particularly preferred.
[0076] The addition of fluoride facilitates the crystallization of iota-alumina. Specifically, the fluoride promotes the decomposition reaction of sodium aluminate (NaAlO2) as an intermediate product, thereby increasing the yield of iota-alumina as the decomposition reaction product and promoting the crystallization of iota-alumina.
[0077] In the following description, the molar ratio of the total of the alkali metal and alkaline earth metal of all raw materials to the boron (B) of the sodium borate is sometimes described as A / B (molar ratio). In the present embodiment, the A / B (molar ratio) of the raw materials is preferably less than 2.65. When A / B is 2.65 or more, the amount of sodium ions in the reaction system becomes excessive and the yield decreases.
[0078] In the reaction step, a product containing iota-alumina is obtained by heating the solid raw material.
[0079] The heating temperature in the reaction process is greater than 450°C. When the heating temperature is set to below 450°C, the crystallization of iota-alumina cannot be fully carried out. In addition, the heating temperature in the reaction process is lower than 710°C. When the heating temperature is set to above 710°C, sodium aluminate (NaAlO2) is generated as an impurity, and the yield decreases. In addition, when the heating temperature reaches above 710°C, sodium borohydride (NaBH4) decomposes, the amount of sodium borohydride melt decreases, and the amount of reaction decreases.
[0080] The heating temperature in the reaction step is preferably set to 490° C. to 610° C. By setting the heating temperature to 490° C. to 610° C., a sufficient reaction rate can be obtained, and the generation efficiency of iota-alumina is excellent. More specifically, by setting the heating temperature to 490° C. or higher, so-called needle-shaped iota-alumina having fine and long crystals is formed, and the product sodium borohydride (NaBH4) is formed into a molten state, which can promote the reaction.
[0081] Even when the heating temperature is lower than 490°C, the aluminum (Al) oxide film will be converted into iota alumina. However, the amount of sodium borohydride melt is significantly reduced, and the rate of formation of iota alumina becomes extremely slow, resulting in so-called rod-shaped iota alumina with coarse and short crystals.
[0082] The reaction process is carried out under a hydrogen-containing gas atmosphere. When a hydrogen atmosphere is formed, the hydrogen pressure is preferably set to a range of 0.5 MPa to 10 MPa, and more preferably set to a range of 0.6 MPa to 1 MPa. By setting the hydrogen pressure to 0.6 MPa to 1 MPa, the generation efficiency of sodium borohydride is excellent, and a reaction vessel, an apparatus, etc. with excellent pressure resistance are not required, and the increase in equipment cost can be suppressed.
[0083] In the reaction step, a formation reaction occurs by heating the solid raw material to generate iota-alumina. The formation reaction of iota-alumina is described in detail below.
[0084] In the initial stage of the reaction, sodium metaborate (NaBO2) contacts aluminum (Al) particles through stirring, and sodium metaborate adheres to the aluminum (Al) particles. Through this adhesion, the aluminum oxide film on the surface of aluminum (Al) absorbs sodium oxide (Na2O) and is converted into sodium metaaluminate (NaAlO2).
[0085] The sodium aluminate (NaAlO2) generated here undergoes iota-alumina due to the catalytic action of fluoride ions. In this way, an iota-alumina oxide film layer with a thickness of about 100nm-2000nm is generated on the surface of the aluminum particles at the beginning of the reaction. As a result, sodium ions can easily pass through the oxide film on the surface of aluminum (Al).
[0086] Sodium aluminate (NaAlO2) is converted into iota-alumina and sodium oxide (Na2O) is generated simultaneously. Thus, aluminum (Al) inside the oxide film layer is oxidized by sodium oxide (Na2O) and converted into aluminum oxide (Al2O3).
[0087] The aluminum oxide (Al2O3) generated on the aluminum surface is fine and highly active, and acts as a Lewis acid. The sodium oxide (Na2O) present around it acts as a Lewis base, and the aluminum oxide (Al2O3) is neutralized and converted into sodium aluminate (NaAlO2). In the presence of fluoride ions, sodium aluminate (NaAlO2) crystallizes into iota-alumina (Na 0.67 Al6O 9.33 ), and sodium oxide (Na2O) is discharged. As a result, iota-alumina is generated inside the initial alumina film, and an iota-alumina layer containing sodium oxide (Na2O) is grown.
[0088] In addition, iota-alumina is produced under the condition that four kinds of ions, namely aluminum ions, oxygen ions, sodium ions and fluoride ions, are dissolved in sodium borohydride. When sodium borohydride is in a liquid state, the diffusion of the above four kinds of ions is promoted, and the growth of iota-alumina becomes faster, so it is easy to obtain iota-alumina with a large aspect ratio.
[0089] The crystal habit of iota-alumina crystals is mostly needle-shaped or rod-shaped. It is speculated that the needle-shaped crystals of iota-alumina occur because of a reaction that occurs during the crystallization process while discharging sodium oxide (Na2O) while growing. In other words, it is speculated that the direction of crystal growth is preferentially in the direction of low sodium oxide (Na2O) concentration, and the iota-alumina crystals become needle-shaped or rod-shaped.
[0090] Here, in the formation reaction of iota-alumina, when the heating temperature in the reaction step is set to 490° C. or higher, a particle diffusion reaction occurs. The particle diffusion reaction will be described below.
[0091] In the oxidation reaction of aluminum inside the above-mentioned oxide film layer, sodium oxide (Na2O) is reduced to sodium (Na). Sodium (Na) reduces hydrogen (H2) to become sodium hydride (NaH). Sodium hydride (NaH) reacts with sodium metaborate (NaBO2) to generate sodium borohydride (NaBH4) and sodium oxide (Na2O).
[0092] In addition, on the surface of aluminum particles, fluoride ions react with aluminum in a portion thereof to form a NaAlF layer containing sodium (Na), aluminum (Al) and fluorine (F) as constituent elements. The NaAlF layer is mainly composed of sodium hexafluoroaluminate (Na3AlF6), and low-grade aluminum fluoride (presumably AlF6) is generated at the interface with aluminum. 1.5 ). Low-grade aluminum fluoride (AlF 1.5 ) has a very strong reducing property, reducing sodium oxide (Na2O) to generate sodium hydride (NaH), aluminum oxide (Al2O3) and sodium fluoride (NaF) in a hydrogen atmosphere. 1.5 ) moves in the system due to its gas pressure, and promotes the reduction reaction of sodium metaborate (NaBO2) particles to sodium borohydride (NaBH4) together with sodium hydride, which is also a gas. As a result, fluoride also helps aluminum to move in the system.
[0093] Sodium borohydride (NaBH4) becomes a melt when the temperature reaches above 490°C. The molten sodium borohydride (NaBH4) fills the iota-alumina layer, and combines sodium hydride, sodium oxide, sodium ions, aluminum ions, fluoride ions, oxygen ions and metaborate ions (BO 2- ) dissolved.
[0094] As a result, the sodium borohydride (NaBH4) in the melt becomes a medium for the movement of substances and a reaction site, and each ion can move inside and outside the oxide layer outside the aluminum particles. As a result, conditions are formed in which reactions can occur inside and outside the iotalumina layer of the aluminum (Al) particles or on the surface of the sodium metaborate (NaBO2) particles.
[0095] At this time, aluminum (Al) particles and sodium metaborate (NaBO2) particles come into contact with each other due to stirring, and the material range including raw materials, product intermediates, and products adheres and detaches on the particle surface. As a result, particles of sodium borohydride (NaBH4), sodium hydride (NaH), sodium oxide (Na2O), sodium metaborate (NaBO2), and aluminum ions can achieve a high-speed movement speed that cannot be achieved by simple diffusion, and the sodium borohydride (NaBH4) generation reaction is promoted.
[0096] As described above, in the iota-alumina formation reaction, not only inside the aluminum (Al) particles, but also due to the contact between the particles, the raw material sodium metaborate (NaBO2), the intermediate products (NaH, Na2O, AlF 1.5 ) and sodium borohydride (NaBH4) as a solvent undergo mass transfer, and some intermediate products (NaH, AlF 1.5 ) turns into gas and moves, and a high-speed reaction also occurs on the surface of each particle and in the particle. In this embodiment, this reaction is called "particle stirring reaction".
[0097] Among them, when the heating temperature in the reaction process is lower than 490°C, sodium borohydride (NaBH4) does not become a melt, and thus passes through the ι-alumina layer more slowly, and the amount of sodium hydride (NaH) seeping out to the outside of the aluminum (Al) particles is greatly reduced. Therefore, in this case, the boron ions that have passed through the ι-alumina layer mainly react with sodium hydride (NaH) inside the oxide layer of the aluminum (Al) particles, and part of the sodium hydride (NaH) that has become a gas reacts with the sodium metaborate (NaBO2) particles.
[0098] The washing step is a step of placing the mixture of solid raw materials into a polar solvent. Through this step, the reaction product can be used to increase the iota-alumina (Na 0.67 Al6O 9.33 Thus, iota-alumina with few impurities can be obtained.
[0099] In the washing process, the mixture of solid raw materials is stirred together with the polar solvent. This can increase the iota-alumina (Na 0.67 Al6O 9.33 ) dissolution rate of substances other than
[0100] The polar solvent is, for example, water, preferably pure water such as ion-exchanged water. Thus, sodium borohydride (NaBH4) as a water-soluble impurity can be appropriately removed from the reaction product. Furthermore, when the polar solvent is water, sodium borohydride (NaBH4), sodium hydride (NaH), sodium fluoride (NaF), lower aluminum fluoride (AlF 1.5 ), sodium borates and sodium aluminate (NaAlO2) are removed from the reaction product.
[0101] Here, the water used as the polar solvent is not limited to pure water, and may also be an acidic or alkaline aqueous solution. At this time, the pH of the water used as the polar solvent is preferably 2 or more and 11 or less. Moreover, the pH of the water used as the polar solvent is more preferably 9 or more. Thus, impurities insoluble in neutral water such as cryolite (Na3AlF6) and aluminum can be further dissolved and removed from the reaction product.
[0102] When the polar solvent is water, the washing process is preferably carried out at 80°C to 100°C. At this time, the dissolution rate of impurities can be increased. In addition, the washing process can also be carried out at room temperature. At this time, blocky iota-alumina in which needle-shaped or rod-shaped iota-alumina crystals account for the majority can be obtained. In the following description of the washing process, unless otherwise specified, high temperature refers to a temperature of 80°C to 100°C, and room temperature refers to a temperature of 5°C to 35°C.
[0103] Figure 1A This is a SEM (Scanning Electron Microscope) reflected electron image of a cross section of a massive reaction product that was washed by stirring it with water at 80° C. to 100° C. for 1 hour. Figure 1B yes Figure 1A The enlarged SEM reflected electron image of the range IB shown. Figure 1A The reaction product involved is the product involved in the later described Experimental Example 7. The block-shaped product is formed because the generated sodium borohydride (NaBH4) becomes a melt and the particles that were originally aluminum particles are bonded to each other. Figure 1B As shown, the surface has a dense oxide layer, and the oxide inside is iota-alumina, which is in the shape of needles (whiskers). The space between the layered iota-alumina layers is the result of sodium borohydride being eluted during cleaning. Unreacted aluminum remains in the center.
[0104] Figure 1C It is observation Figure 1A An enlarged SEM reflection electron image of iota-alumina crystals obtained by observing the surface of the product involved. Figure 1D is different from Figure 1C Observation of the parts Figure 1A The surface of the product involved is obtained by the magnified SEM reflection electron image of the iota-alumina crystal. When the growth rate of iota-alumina is fast, Figure 1C As shown, it forms an elongated shape, and when it is slow, Figure 1D The needle-shaped iota-alumina crystals thus obtained have a width of 0.05 μm to 0.5 μm, a length of 0.5 μm to 4 μm, and an aspect ratio of 3.4 to 24.5.
[0105] Here, the aspect ratio refers to the ratio of the length W to the width H, that is, the value obtained by dividing the length W by the width H. Figure 1E express Figure 1C The enlarged SEM reflected electron image of the iota-alumina crystals in the range IE shown. Figure 1E As shown, in the SEM reflected electron image, the dimension W in the direction in which the iota-alumina crystal C extends is measured as the length, and the dimension H in the direction perpendicular to the electron image is measured as the width. The aspect ratio of one iota-alumina crystal C can be calculated from this.
[0106] The average aspect ratio of the iota-alumina crystals is not less than 3 and not more than 30. The average aspect ratio of the iota-alumina crystals refers to the arithmetic average of the aspect ratios of a plurality of iota-alumina crystals. Figure 1F Yes means Figure 1D The magnified SEM reflected electron image of the iota-alumina crystals with measured aspect ratios in the range IF shown. Figure 1FAs shown in FIG. 1 , when calculating the average aspect ratio, among the crystal habits presented in the SEM reflected electron image within a specified range, the results of multiple straight lines that are clearly presented are selected as ι-alumina crystals C. In other words, among the crystal habits presented in the SEM reflected electron image within a specified range, those that are not clearly presented as straight line structures are not selected as ι-alumina crystals C. Here, as Figure 1F As shown, the shooting range of the SEM reflected electron image used to calculate the average aspect ratio is set to a range that can select at least 10 ι-alumina crystals C.
[0107] In addition, when the average aspect ratio is calculated using multiple shooting ranges, if the average aspect ratio calculated for at least one shooting range is greater than 3 and less than 30, it can be considered that the average aspect ratio of the iota alumina crystal is greater than 3 and less than 30.
[0108] Figure 1G and Figure 1H This is an enlarged SEM reflection electron image of iota-alumina crystals involved in the product using potassium metaborate (KBO2) as the alkali metal compound as the raw material. Figure 1G and Figure 1H The reaction product involved is the product involved in Test Example 25 described later. Figure 1H is different from Figure 1G When potassium borates are used as raw materials, the following is obtained: Figure 1G The flat iota-alumina and Figure 1H The rod-shaped iota-alumina is shown.
[0109] The thickness of the plate-like iota-alumina crystal thus obtained is 0.018 μm to 0.047 μm, the width is 0.499 μm to 1.111 μm, and the aspect ratio is 12.8 to 60.5. Here, the width of the plate-like iota-alumina refers to the thickness of the iota-alumina crystal, and the width of the plate-like iota-alumina refers to the length in the direction perpendicular to the thickness. Figure 1G The average aspect ratio within the captured range was calculated to be 25.4.
[0110] The rod-shaped iota-alumina crystals thus obtained have a width of 0.298 μm to 0.400 μm, a length of 0.879 μm to 1.444 μm, and an aspect ratio of 2.4 to 4.0. Figure 1F The average aspect ratio within the captured range was calculated to be 3.34.
[0111] Figure 2This is a SEM reflection electron image of powdered iota-alumina crystals obtained by washing the reaction product with boiling water. In the washing process, the water as a polar solvent does not need to be boiled. That is, the reaction product can also be washed by boiling water. In this case, Figure 2 As shown, a powdery iota alumina having needle-shaped or rod-shaped iota alumina crystals located on the surface and a particle size of about 1 μm to about 100 μm is obtained.
[0112] In addition, the polar solvent is not limited to water, and diglyme (diethylene glycol dimethyl ether) may also be used. In this case, sodium borohydride (NaBH4) as an impurity can also be appropriately removed from the reaction product.
[0113] The first to fourth production methods as specific examples of the production method of iota-alumina involved in this embodiment are described in detail below. In the following processes, unless otherwise specified, the process is described using sodium fluoride as the fluoride and sodium metaborate (NaBO2) separated in a crystalline form as the sodium borate. However, the first to fourth production methods described below are ultimately just examples and are not limited to them.
[0114] [First Manufacturing Method]
[0115] Figure 3 : is a process diagram showing the first manufacturing method of iota-alumina. In the manufacturing method of sodium borohydride involved in the first manufacturing method, aluminum powder and fluoride powder are mixed, preheated at a temperature of 100°C to 330°C, and then mixed with sodium borate, placed in a sealed container, and reacted at 490°C to 610°C in a sealed container filled with hydrogen, and then the reaction product is washed. Here, sodium borates and aluminum powders react while maintaining solid phase states. The manufacturing method of sodium borohydride of the first manufacturing method is as follows: Figure 3 As shown, the process includes the first step (S-11) to the fourth step (S-14). Here, the first step (S-11) to the third step (S-13) are examples of "reaction steps", and the fourth step (S-14) is an example of "cleaning step".
[0116] (a) First step
[0117] As a pretreatment process, aluminum powder and sodium fluoride are mixed and rubbed against each other. After treatment, they are placed in a container and covered, and after forming an atmosphere with a humidity of less than 10%, they are placed in a furnace and heated for more than 30 minutes in an atmosphere of 100°C to 330°C, so that aluminum (Al) and sodium fluoride (NaF) release moisture and form an aluminum oxide film on the particle surface of aluminum (Al) powder 52.
[0118] After the powder subjected to the above heat treatment is cooled, it is mixed with sodium borate powder. After or before the mixed powder is placed in a sealed container, a non-oxidizing gas is introduced into the sealed container to fill the interior with a non-oxidizing gas atmosphere. These steps are the first step (S-11).
[0119] That is, in the first step, aluminum and sodium fluoride are mixed (premixed) in advance, and after heat treatment, all the mixed raw materials are placed in a sealed container. In the first step, by treating in an atmosphere with a humidity of less than 10%, it is possible to prevent moisture in the air from adhering to aluminum and fluoride and oxidation of aluminum. After the treated powder is mixed with sodium borate powder and placed in a sealed container, the timing for filling the sealed container with a non-oxidizing gas atmosphere may be after the raw materials are placed in the sealed container or before the materials are placed in the sealed container.
[0120] In the first step, the temperature in the sealed container when the raw materials are charged is not particularly limited, but the workability is good when it is lower than 100°C.
[0121] As the sealed container in the first step, a container having heat resistance and pressure resistance capable of withstanding high temperature (e.g., 610° C.) and high pressure (e.g., 10 MPa) and capable of ensuring a sealed space for filling gas is used. The sealed container has a stirring unit. The details of the sealed container will be described later.
[0122] (b) Second step
[0123] Figure 3 The second step (S-12) shown is a step of placing all raw materials in a sealed container, heating the sealed container to 400°C to 610°C, removing residual water contained in sodium borate and aluminum powder, and causing the water that cannot be removed to react with aluminum to convert into hydrogen and aluminum oxide film, thereby removing water. The aluminum fluoride (AlF3) generated in the first step is thus heated at high temperature to become cryolite (Na3AlF6), forming a NaAlF layer. The second step is a step of reacting vaporized water (i.e., residual water contained in the raw materials in the sealed container) with aluminum, or a step of removing water from the reaction system by evacuating with a vacuum pump, and converting the aluminum fluoride generated on the surface of the aluminum into cryolite.
[0124] When the heating temperature is set to 530°C in the second step, the formation of cryolite (Na3AlF6) from aluminum fluoride (AlF3) takes about 30 minutes or more. Here, when sodium metaborate dried to a moisture content of about 0% to 3% is used as a raw material, the dehydration reaction is completed in about 0.5 to 1 hour.
[0125] (c) Third step
[0126] Figure 3The third step (S-13) shown is a step of heating the sealed container to 490°C to 610°C and introducing hydrogen. By heating, the oxide film and sodium aluminate (NaAlO2) on the aluminum surface are converted into needle-shaped iota-alumina due to the diffusion of sodium oxide and the crystallization of aluminum oxide caused by fluoride. When sodium oxide reaches the surface of aluminum (Al), it is reduced by aluminum and begins to generate sodium hydride (NaH). When sodium hydride (NaH) diffuses in iota-alumina and contacts sodium borate, the sodium borohydride reaction begins. When sodium borohydride fills the iota-alumina layer, sodium hydride (NaH), sodium oxide (Na2O), aluminum ions, borate ions, etc. can move with sodium borohydride as a solvent, and the "particle stirring reaction" begins. The particle stirring reaction can achieve material movement only by particle contact, so weak stirring is sufficient. The stirring unit in the sealed container is rotated to stir. The reaction product is obtained in this way.
[0127] In the third step, the particle stirring reaction is to make the powders maintained in the solid phase contact with each other and react on the surface of aluminum, and then the products and raw materials are moved by diffusion, and the synthesis is carried out by continuous reaction. However, in order to further assist the movement of these substances, transportation energy can also be provided by stirring.
[0128] In the third step, as the reaction proceeds, the amount of hydrogen in the reaction container decreases, but the reaction rate increases by increasing the hydrogen pressure. The reaction here is represented by the following reaction formula (2).
[0129] 4Al+6H2+3NaBO2→3NaBH4+2Al2O3···(2)
[0130] In the third step, the sealed container may be the same as that used in the first step to the second step, or another sealed container may be used. That is, the first step to the third step may be performed as a process in one sealed container, or as a process in different sealed containers.
[0131] (d) Fourth step
[0132] Figure 3 The fourth step (S-14) shown is a step of washing the reaction product with a polar solvent. The polar solvent is water. In the fourth step, the reaction product and water are stirred at 50°C to 100°C for more than 30 minutes. Thus, sodium borohydride (NaBH4), sodium hydride (NaH), sodium fluoride (NaF), low-grade aluminum fluoride (AlF 1.5), sodium borates and sodium aluminate (NaAlO2) are dissolved from the reaction product into a polar solvent. Then, the reaction product is taken out from the solvent and dried under reduced pressure. In the fourth step, when an alkaline aqueous solution is used as a polar solvent, cryolite (Na3AlF6) and aluminum can be dissolved in addition to the above substances. At this time, iota-alumina and aluminum hydroxide remain as solids, so it is easier to take out iota-alumina.
[0133] Through the above-mentioned first to fourth steps, iota-alumina can be generated.
[0134] The following is a description of another manufacturing method, but description of the same points as the first manufacturing method will be omitted.
[0135] [Second Manufacturing Method]
[0136] Figure 4 This is a process diagram showing a second manufacturing method of iota-alumina. In the second manufacturing method of sodium borohydride, aluminum powder 52, sodium hydroxide powder 55 and fluoride powder 54 are mixed, preheated at a temperature of 100°C to 330°C, and then mixed with sodium borate powder 51. After being placed in a sealed container, the mixture is heated at 400°C to 610°C and the moisture is removed by a vacuum pump. After that, hydrogen is introduced and the mixture is reacted at 490°C to 610°C in a sealed container filled with hydrogen. Sodium borate powder 51 and aluminum powder 52 react while maintaining a solid phase state. The second manufacturing method of sodium borohydride is as follows. Figure 4 As shown, the process includes the first step (S-21) to the fourth step (S-24). Here, the first step (S-21) to the third step (S-23) are examples of "reaction steps", and the fourth step (S-24) is an example of "cleaning step".
[0137] (a) First step
[0138] As a pretreatment process, aluminum powder 52, fluoride powder 54 and sodium hydroxide powder 55 are mixed and rubbed against each other. After treatment, they are placed in a container and covered. After forming an atmosphere with a humidity of less than 10%, they are placed in a furnace and heated for more than 30 minutes in an atmosphere of 100°C to 330°C, so that part of the water contained in the sodium hydroxide is released to the aluminum (Al) and sodium fluoride (NaF), and an aluminum oxide film and sodium oxide (Na2O) are generated on the particle surface of the aluminum (Al) powder 52. At this time, since there is a lot of water from the sodium hydroxide and sodium oxide exists on the surface of the aluminum, the oxidation of aluminum proceeds first. Therefore, the reaction of generating aluminum fluoride from hydrogen fluoride occurs very little.
[0139] After the powder subjected to the above heat treatment is cooled, it is mixed with sodium borate powder. After or before the mixed powder is placed in a sealed container, a non-oxidizing gas is introduced into the sealed container to fill the interior with a non-oxidizing gas atmosphere. These steps are the first step (S-21).
[0140] That is, in the first step, aluminum and sodium hydroxide are mixed (premixed) in advance, and after heat treatment, all the mixed raw materials are placed in a sealed container. In the first step, by treating in an atmosphere with a humidity of less than 10%, it is possible to prevent moisture in the air from adhering to aluminum, sodium hydroxide and fluoride and oxidation of aluminum. After the treated powder is mixed with the sodium borate powder, the timing for filling the sealed container with a non-oxidizing gas atmosphere may be after or before the raw materials are placed in the sealed container.
[0141] (b) Second step
[0142] Figure 4 The second step (S-22) shown is a step of placing all the mixed raw materials into a sealed container, heating the sealed container to a temperature of 400°C to 610°C, removing the residual water contained in the sodium hydroxide, sodium borate, aluminum powder and fluoride powder, and allowing the water that cannot be removed to react with aluminum to convert into hydrogen and aluminum oxide film to remove the water. At this time, the sodium hydroxide attached to the aluminum surface becomes sodium oxide. In addition, part of the sodium oxide reacts with the oxide film on the aluminum surface to become sodium aluminate (NaAlO2). The second step is a step of allowing the residual water contained in the raw materials in the sealed container to react with aluminum, or a step of removing water from the reaction system by evacuating with a vacuum pump.
[0143] (c) Third step
[0144] Figure 4 The third step (S-23) shown is a step of heating the sealed container to 490°C to 610°C and introducing hydrogen. By heating, the oxide film and sodium aluminate (NaAlO2) on the aluminum surface are converted into needle-shaped iota-alumina due to the diffusion of sodium oxide and the crystallization of aluminum oxide by fluoride. When sodium oxide reaches the surface of aluminum (Al), it is reduced by aluminum and begins to generate sodium hydride (NaH). When sodium hydride (NaH) diffuses in iota-alumina and contacts sodium borate, the sodium borohydride reaction begins. When sodium borohydride fills the iota-alumina layer, sodium hydride (NaH), sodium oxide (Na2O), aluminum ions, borate ions, etc. can move with sodium borohydride as a solvent, and the "particle stirring reaction" begins. The particle stirring reaction can achieve material movement only by particle contact, so weak stirring is sufficient. The stirring unit in the sealed container is rotated to stir. The reaction product is obtained in this way.
[0145] (d) Fourth step
[0146] Figure 4 The fourth step (S-24) shown is a step of washing the reaction product with a polar solvent. The polar solvent is water. In the fourth step, the reaction product and water are stirred at 80°C to 100°C for more than 30 minutes. Thus, sodium borohydride (NaBH4), sodium hydride (NaH), sodium fluoride (NaF), and low-grade aluminum fluoride (AlF 1.5 ), sodium borates and sodium aluminate (NaAlO2) are dissolved from the reaction product into a polar solvent. Then, the reaction product is taken out from the solvent and dried under reduced pressure.
[0147] [Third Manufacturing Method]
[0148] Figure 5 This is a process diagram showing a third manufacturing method of iota-alumina. In the third manufacturing method of sodium borohydride, aluminum powder 52 and sodium hydroxide powder 55 are mixed, preheated at a temperature of 100°C to 330°C, and then mixed with fluoride powder 54 and sodium borate powder 51. After being placed in a sealed container, the mixture is heated at 400°C to 610°C and the moisture is removed by a vacuum pump. Thereafter, hydrogen is introduced and the mixture is reacted at 490°C to 610°C in a sealed container filled with hydrogen. Sodium borate powder 51 and aluminum powder 52 react while maintaining a solid phase state. The third manufacturing method of sodium borohydride is as follows. Figure 5 As shown, the process includes the first step (S-31) to the fourth step (S-34). Here, the first step (S-31) to the third step (S-33) are examples of "reaction steps", and the fourth step (S-34) is an example of "cleaning step".
[0149] (a) First step
[0150] As a pretreatment process, aluminum powder 52 and sodium hydroxide powder 55 are mixed and rubbed against each other. After treatment, they are placed in a container and covered, and after forming an atmosphere with a humidity of less than 10%, they are placed in a furnace and heated for more than 30 minutes in an atmosphere of 100°C to 330°C, so that part of the water contained in the sodium hydroxide is released to the aluminum (Al), and an aluminum oxide film and sodium oxide (Na2O) are formed on the particle surface of the aluminum (Al) powder 52.
[0151] After cooling, the powder subjected to the above heat treatment is mixed with sodium borate powder and fluoride powder. After or before the mixed powder is placed in a sealed container, a non-oxidizing gas is introduced into the sealed container to fill the interior with a non-oxidizing gas atmosphere. The above process is the first process (S-31).
[0152] That is, in the first step, aluminum and sodium hydroxide are mixed (premixed) in advance, and after heat treatment, all the mixed raw materials are placed in a sealed container. In the first step, by treating in an atmosphere with a humidity of less than 10%, it is possible to prevent moisture in the air from adhering to aluminum, sodium hydroxide and fluoride and oxidation of aluminum. After the treated powder is mixed with the sodium borate powder, the timing for filling the sealed container with a non-oxidizing gas atmosphere may be after or before the raw materials are placed in the sealed container.
[0153] (b) Second step
[0154] Figure 5 The second step (S-32) shown is a step of placing all the mixed raw materials into a sealed container, heating the sealed container to a temperature of 400°C to 610°C, removing the residual water contained in the sodium hydroxide, sodium borate, aluminum powder and fluoride powder, and allowing the water that cannot be removed to react with aluminum to convert into hydrogen and aluminum oxide film, thereby removing the water. The sodium hydroxide attached to the aluminum surface is converted into sodium oxide. Part of the sodium oxide reacts with the oxide film on the aluminum surface to become sodium aluminate (NaAlO2). The second step is a step of reacting the residual water contained in the raw materials in the sealed container with aluminum, or a step of removing water from the reaction system by evacuating air using a vacuum pump.
[0155] (c) Third step
[0156] Figure 5 In the third step (S-33) shown, the sealed container is heated to 490°C to 610°C and hydrogen gas is introduced. By heating, the oxide film and sodium aluminate (NaAlO2) on the aluminum surface are converted into needle-shaped iota-alumina due to the diffusion of sodium oxide and the crystallization of aluminum oxide by fluoride. When sodium oxide reaches the surface of aluminum (Al), it is reduced by aluminum and begins to generate sodium hydride (NaH). When sodium hydride (NaH) diffuses in iota-alumina and contacts sodium borate, the sodium borohydride reaction begins. When sodium borohydride fills the iota-alumina layer, sodium hydride (NaH), sodium oxide (Na2O), aluminum ions, borate ions, etc. can move with sodium borohydride as a solvent, and the "particle stirring reaction" begins. The particle stirring reaction can achieve material movement only by particle contact, so weak stirring is sufficient. The stirring unit in the sealed container is rotated to stir. In this way, a reaction product is obtained.
[0157] (d) Fourth step
[0158] Figure 5The fourth step (S-34) shown is a step of washing the reaction product with a polar solvent. The polar solvent is water. In the fourth step, the reaction product and water are stirred at 80°C to 100°C for more than 30 minutes. Thus, sodium borohydride (NaBH4), sodium hydride (NaH), sodium fluoride (NaF), and low-grade aluminum fluoride (AlF 1.5 ), sodium borates and sodium aluminate (NaAlO2) are dissolved from the reaction product into a polar solvent. Then, the reaction product is taken out from the solvent and dried under reduced pressure.
[0159] [Fourth Manufacturing Method]
[0160] Figure 6 This is a process diagram of the fourth manufacturing method for manufacturing ι-alumina. In the fourth manufacturing method for manufacturing sodium borohydride, in the first step, aluminum powder 52, sodium hydroxide powder 55, fluoride powder 54 and sodium borate powder 51 are mixed, put into a sealed container, filled with non-oxidizing gas and then sealed; in the second step, the sealed container is heated to a temperature of 400°C to 610°C in a sealed state, so that the moisture generated by the raw materials reacts with the fluoride to generate gaseous hydrogen fluoride, which reacts with aluminum to form aluminum fluoride on the aluminum surface; then, in the third step, the reaction is carried out in a sealed container filled with hydrogen at a temperature of 490°C to 610°C. Sodium borates and aluminum powders react while maintaining a solid phase state. The fourth manufacturing method for manufacturing sodium borohydride is as follows. Figure 6 The process shown includes the first step (S-41) to the fourth step (S-44). Here, the first step (S-41) to the third step (S-43) are examples of "reaction steps", and the fourth step (S-44) is an example of "cleaning step".
[0161] (a) First step
[0162] As a pretreatment process, aluminum powder 52, sodium hydroxide powder 55 and fluoride powder 54 are mixed and rubbed together in an atmosphere with a humidity of less than 10%, and then sodium borate powder 51 is mixed. After they are placed in a sealed container, a non-oxidizing gas is introduced into the sealed container after or before the sealed container is placed, so that the inside is filled with a non-oxidizing gas atmosphere. The above process is the first process (S-41). The timing for introducing the non-oxidizing gas may be after or before the raw materials are placed in the sealed container. However, the method of mixing the raw materials is not limited to this, and all the raw materials of aluminum powder 52, sodium hydroxide powder 55, fluoride powder 54 and sodium borate powder 51 may be mixed and rubbed together at the same time.
[0163] (b) Second step
[0164] Figure 6The second step (S-42) shown is a step of heating the sealed container to a temperature of 400°C to 610°C after sealing the sealed container, so that the residual water contained in the sodium hydroxide, sodium borate, aluminum powder and fluoride powder reacts with aluminum (Al) to remove the water. It is also a step of using high-temperature water to react with fluoride to generate hydrogen fluoride (HF) vapor, thereby generating aluminum fluoride on the aluminum surface. At this time, sodium hydroxide becomes sodium oxide. In addition, part of the sodium oxide reacts with the oxide film on the aluminum surface to become sodium aluminate (NaAlO2). The second step is a step of removing the residual water contained in the raw materials in the sealed container and generating aluminum fluoride.
[0165] (c) Third step
[0166] Figure 6 The third step (S-43) shown is a step of heating the sealed container to 490°C to 610°C and introducing hydrogen. By heating, the oxide film and sodium aluminate (NaAlO2) on the aluminum surface are converted into needle-shaped iota-alumina due to the diffusion of sodium oxide and the crystallization of aluminum oxide brought by fluoride. When sodium oxide reaches the aluminum (Al) surface, it is reduced by aluminum and begins to generate sodium hydride (NaH). When sodium hydride (NaH) diffuses in iota-alumina and contacts sodium borate, the sodium borohydride reaction begins. When sodium borohydride fills the iota-alumina layer, sodium hydride (NaH), sodium oxide (Na2O), aluminum ions, borate ions, etc. can move with sodium borohydride as a solvent, and the "particle stirring reaction" begins. The aluminum fluoride that appeared on the aluminum surface in the second step absorbs the diffused sodium ions and becomes cryolite (Na3AlF6), forming a NaAlF layer on the aluminum surface. At the interface between the NaAlF layer and Al, low-order aluminum fluoride (AlF 1.5 ), as a substance with strong reducing properties and as a substance that can move in the form of vapor, it moves in the system, reacts with sodium oxide (Na2O) to generate sodium hydride (NaH) and aluminum oxide, and assists the generation of sodium borohydride. The particle stirring reaction can achieve material movement only through particle contact, so weak stirring is sufficient. The stirring unit in the closed container is rotated for stirring. Thus, a reaction product is obtained.
[0167] (d) Fourth step
[0168] Figure 6 The fourth step (S-44) shown is a step of washing the reaction product with a polar solvent. The polar solvent is water. In the fourth step, the reaction product and water are stirred at 80°C to 100°C for more than 30 minutes. Thus, sodium borohydride (NaBH4), sodium hydride (NaH), sodium fluoride (NaF), and low-grade aluminum fluoride (AlF 1.5), sodium borates and sodium aluminate (NaAlO2) are dissolved from the reaction product into a polar solvent. Then, the reaction product is taken out from the solvent and dried under reduced pressure.
[0169] (Sealed container)
[0170] Here, an example of a sealed container that can be used in the first to fourth manufacturing methods is shown.
[0171] Figure 7 This is a partial cross-sectional view showing an example of a closed container used in the first to fourth manufacturing methods.
[0172] like Figure 7 As shown, the sealed container 10A has a bottomed cylindrical container body 12 with a round bottom, and a disc-shaped cover 14 that can be attached and detached to seal the container body 12. A heater 16 capable of adjusting the temperature is arranged on the outer side of the lower part of the container body 12, and the content of the container body 12 is heated by the heater 16. In addition, an O-ring 18 is arranged on the upper end surface of the container body 12 to closely fit with the cover 14 to ensure the airtightness of the interior. When the cover 14 is tightly closed, the cover 14 forms a state of being closely fitted with the O-ring 18 relative to the container body 12.
[0173] The cover 14 has an opening at its center, and a cylindrical portion is vertically arranged near the opening, and a motor 20 is arranged on the upper side of the cylindrical portion. The stirring device has the motor 20, a stirring rod 22 connected to the rotating shaft of the motor 20, and a plurality of pin-shaped stirring elements 22A arranged in a direction perpendicular to the axis of the stirring rod 22. When the cover 14 is mounted on the container body 12, the front end of the stirring rod 22 reaches the lower area inside the container body 12. That is, when the motor 20 is driven, the pin-shaped stirring element 22A rotates together with the stirring rod 22 to stir the contents of the container body 12.
[0174] The cover 14 further includes a first conduit 24 and a second conduit 30 that communicate with the interior of the container body 12. The first conduit 24 is connected to a hydrogen supply source (not shown) via a hydrogen supply valve 26 and is connected to a vacuum pump (not shown) via an exhaust valve 28. That is, when the hydrogen supply valve 26 is in an open state, hydrogen is supplied to the interior of the container body 12; when the exhaust valve 28 is in a closed state, the interior of the container body 12 is evacuated. In addition, the second conduit 30 is connected to a pressure gauge 32, and the pressure in the container body 12 can be obtained through the pressure gauge 32.
[0175] Figure 8 FIG. 2 is a partial cross-sectional view showing another example of the sealed container used in the first to fourth manufacturing methods. Figure 7The difference from the sealed container 10A is that in the sealed container 10B, a plurality of plate-shaped scrapers 35 are provided at the lower end of the stirring rod 22 rotating inside the container body 12, forming a multi-blade scraper (MB).
[0176] Fig.11A is used Figure 8 The sealed container 10B shown is a front view of the appearance of a stirrer having a plate-shaped (blade) stirrer. Fig. 11B is used Figure 8 The sealed container 10B shown is a side view photograph of the appearance of a stirrer having a plate-shaped (blade) stirrer. Fig. 12A is used Figure 8 The photograph of the closed container and the blade stirring bar after the reaction product is taken out of the container after the stirring for a predetermined time is shown. Fig. 12B is used Figure 8 The closed container shown in the figure shows a photograph of the reaction product after the specified stirring time is completed and the product is taken out of the container. Fig. 12A As shown, the agglomerated reaction products remaining on the scraper and the adhesion layer adhering to the container wall can be confirmed.
[0177] Fig. 9 FIG. 1 is a partial cross-sectional view showing another example of the sealed container used in the first to fourth manufacturing methods. Figure 7 The difference from the sealed container 10A is that in the sealed container 10C, a strip-shaped scraper 36 is provided at the lower end of the stirring rod 22 rotating inside the container body 12.
[0178] Fig.10 FIG. 1 is a partial cross-sectional view showing another example of the sealed container used in the first to fourth manufacturing methods. Fig.10 In the closed container 10D shown in the figure, the container body 12 is set to a horizontal position, and a wide paddle stirring rod 37 is provided on the stirring rod 22 rotating inside the container body 12b via a support portion, which is different from the Figure 7 When a wide paddle stirrer 37 such as the closed container 10D is used for stirring, the raw material is scooped up by the paddle surface when the wide paddle stirrer 37 rotates. In the process of scooping up the raw material by the paddle surface or in the process of the scooped raw material falling, the particles of the raw material collide with each other, and a good particle stirring reaction occurs.
[0179] Fig.13A Yes Fig.10 A photograph of a closed vessel before the horizontal wide paddle (WP) stirring bar is rotated to produce iota-alumina. Fig. 13B Yes Fig.10 A photograph of a closed container after production of iota-alumina with a horizontal wide paddle (WP) stirring bar rotating is shown.
[0180] An example of a sealed container that can be used in the first to fourth production methods has been described above, but the present embodiment is not limited to the above case. For example, a ball mill that can be heated and introduced with hydrogen can also be used as a sealed container.
[0181] (Function of fluoride)
[0182] The role of fluoride in the first to fourth production methods of iota-alumina production process will be described in detail below with reference to the drawings.
[0183] As mentioned above, the role of fluoride is to promote the formation of sodium hydride (NaH), thereby increasing the amount of iota-alumina produced. Specifically, fluoride has two effects on aluminum.
[0184] The first effect is to promote the crystallization of aluminum oxide. This can inhibit the dissolution of aluminum ions from aluminum oxide. As a result, the aluminum ions from the reaction system decrease, and the sodium ion concentration in the reaction system increases relatively. Therefore, when the activity of sodium ions increases, the reducing property of aluminum increases, which can increase the generation of sodium hydride (NaH).
[0185] The second function is to form a NaAlF layer on the surface of aluminum particles to generate low-grade aluminum fluoride (AlF 1.5 ) action. The lower aluminum fluoride moves from the aluminum surface to the outside and reduces the sodium oxide (Na2O). As a result, the amount of sodium hydride (NaH) generated increases. In addition, the lower aluminum fluoride (AlF 1.5 ) has a gas pressure at the formation reaction temperature of iota-alumina and can also move in the form of gas. Sodium hydride (NaH) also has a gas pressure and can move with low-grade aluminum fluoride (AlF 1.5 ) move toward the sodium borate particles to form sodium borohydride.
[0186] FIG. 14A to FIG. 14F Schematic diagram of the reaction of forming iota-alumina. The following is a reaction diagram of the role of fluoride in each process, taking the first to fourth production methods using sodium fluoride (NaF) as an example, referring to the reaction diagram ( FIG. 14A to FIG. 14F ) The formation process of iota-alumina is described in detail. However, the effects described below are not limited to sodium fluoride. That is, fluorides other than sodium fluoride can also form fluoride ions in the reaction system, and thus have the same effect as sodium fluoride.
[0187] 1) Water removal and aluminum surface modification (second process)
[0188] like Fig.14AAs shown, in the second step, the reaction container is sealed, and the generated water reacts with fluoride to generate hydrogen fluoride, which then reacts with aluminum to form a NaAlF layer with cryolite (Na3AlF6) as the main component on the aluminum surface.
[0189] When sodium hydroxide (NaOH) is added, the added sodium hydroxide (NaOH), sodium borates and residual water in the aluminum oxide film 101b are removed in the second step, and sodium oxide is generated from the sodium hydroxide, which reacts with aluminum to form sodium aluminate (NaAlO2).
[0190] 2) Initial stage of reaction - 1 (third step)
[0191] like Fig. 14B As shown in FIG. 1 , sodium aluminate (NaAlO2) 106 formed on the surface 101a of the aluminum (Al) particle is transformed into needle-shaped iota-alumina (Na 0.67 Al6O 9.33 )101c layer and sodium oxide (Na2O).
[0192] 3) Initial stage of reaction - 2 (third step)
[0193] like Fig. 14C As shown, in the needle-shaped iota-alumina (Na 0.67 Al6O 9.33 )101c layer, mainly hydrogen gas (H2) from the atmosphere and sodium ions (O 2- ) moves, but other ions also move between the needle-shaped crystals of iota-alumina and reach the inside of the iota-alumina layer. Due to the presence of sodium oxide (Na2O) generated in the initial stage of the reaction and hydrogen, sodium ions, borate ions, oxygen ions, and fluoride ions moving from the iota-alumina layer, the needle-shaped iota-alumina (Na 0.67 Al6O 9.33 ) 101c layer, the reaction of sodium oxide (Na2O) being reduced by aluminum continues to occur. Through this reaction, sodium hydride (NaH) 112 and aluminum oxide (Al2O3) are generated, and aluminum oxide immediately turns into sodium aluminate (NaAlO2). Due to the catalytic effect of fluoride ions, sodium aluminate (NaAlO2) is decomposed into iota-alumina (Na 0.67 Al6O 9.33 )101c and sodium oxide (Na2O)113.
[0194] Sodium hydride (NaH) reacts with boric acid (B2O3) to produce sodium borohydride (NaBH4)111 and sodium oxide (Na2O).
[0195] Sodium borohydride (NaBH4) as a melt is combined with sodium hydride (NaH)112 to form needle-shaped iota-alumina (Na 0.67 Al6O 9.33 )101c layer. 0.67 Al6O 9.33 ) The layer 101c mainly contains sodium borohydride (NaBH4) of sodium hydride (NaH) and moves to the outside.
[0196] 4) Mid-stage reaction (third step)
[0197] like Fig.14D As shown, the particles are stirred and reacted, and needle-shaped iota-alumina (Na 0.67 Al6O 9.33 )101c layer, from the inside of the aluminum particles, mainly sodium hydride (NaH), aluminum ions (Al 3+ ), metaborate ions (BO 2- ), oxygen ions (O 2- ), sodium ions (O 2- ) each move, starting at the needle-shaped iota-alumina (Na 0.67 Al6O 9.33 )101c reacts on both the inner and outer sides of the layer. The reaction on the sodium metaborate particles is a reaction in which sodium borohydride (NaBH4) containing sodium hydride (NaH) reacts with boric acid (B2O3) to generate sodium borohydride (NaBH4) and sodium oxide (Na2O). At this time, the reaction becomes a cyclic reaction in which sodium oxide (Na2O) contacts aluminum particles again due to stirring.
[0198] 5) Active reaction period (third step)
[0199] like Fig.14E As shown, by stirring, the substances on the surface of the aluminum particles and the sodium metaborate particles are exchanged between the particles, thereby forming a particle stirring reaction. Through repeated contact between the particles, sodium metaborate (NaBO2) 102 and the reaction product sodium oxide (Na2O) are supplied from the particles of sodium metaborate 102 to the aluminum particles 101. On the other hand, the reaction products (sodium borohydride (NaBH4) 111, sodium hydride (NaH) 112) are supplied from the particles of aluminum 101 to the particles of sodium metaborate (NaBO2) 102. By stirring the particles, such material exchange is carried out at a high speed, the particle stirring reaction progresses, and the aluminum particles gradually absorb fragments of sodium metaborate and grow. On the other hand, the sodium metaborate particles also absorb sodium hydride and are transformed into sodium borohydride (NaBH4) and sodium oxide.
[0200] 6) End of reaction (third step)
[0201] like Fig.14F As shown, in the second half of the reaction, the raw materials aluminum, sodium oxide (Na2O) and boric acid (B2O3) are consumed, and the particles become products sodium borohydride (NaBH4) and ι-alumina.
[0202] As the concentration decreases, the amount of sodium hydride generated by aluminum reduction of sodium oxide decreases, and the reaction rate decreases.
[0203] On the other hand, the reducing substance (presumably lower aluminum fluoride = AlF) generated at the interface between aluminum (Al) and the NaAlF layer of the main body of sodium hexafluoroaluminate (Na3AlF6) 1.5 )117 is independent of the concentration of sodium oxide and can be continuously generated. Low-grade aluminum fluoride sublimates and can move, so reducing sodium oxide to generate sodium hydride (NaH)112 can increase the yield of sodium borohydride (NaBH4) in the second half of the reaction. As a result, aluminum (Al)101 particles and sodium metaborate particles become sodium borohydride (NaBH4)111 and needle-shaped iota-alumina (Na)117 as reaction products. 0.67 Al6O 9.33 )101c layer.
[0204] (Test example)
[0205] Hereinafter, the present embodiment will be described in more detail using test examples for illustrating the effects of the present embodiment, but the present embodiment is not limited to these test examples.
[0206] Table 1 is a table showing the materials and manufacturing conditions of Test Examples 1 to 25. In the test, the products involved in Test Examples 1 to 25 were synthesized using the materials and manufacturing conditions shown in Table 1. In Table 1 and the following description, Na / B or Na / B ratio refers to the A / B (molar ratio) when the alkali metal and alkaline earth metal contained in the raw material are only sodium (Na), and K / B ratio refers to the A / B (molar ratio) when the alkali metal and alkaline earth metal contained in the raw material are only potassium (K). In addition, in Table 1 and the following examples, "pure water" refers to ion exchange water, and the pH of the ion exchange water is 5.5 or more and 7.5 or less.
[0207] [Table 1]
[0208]
[0209] Table 2 is a list of substances detected in the products obtained by the production methods involved in Test Examples 1 to 23. Table 3 is a list of substances detected in the products obtained by the production methods involved in Test Examples 24 and 25. The products involved in Test Examples 1 to 25 were subjected to powder X-ray diffraction measurement, and the substances shown in Table 2 or Table 3 were identified. Here, unless otherwise specified, the powder X-ray diffraction measurement was performed at room temperature and pressure, that is, in air at 5°C or above and 35°C or below and 1atm. The intensity of the peak derived from the contained substance in the diffraction spectrum of the product depends on the component ratio of the contained substances in the product, and the contained substance that appears as a strong peak and is clearly contained is determined as "A"; the contained substance that appears as a peak smaller than the contained substance determined by A and is estimated to be small in content is determined as "B"; the contained substance that appears as a peak smaller than the contained substance determined by B and is estimated to be a trace amount is determined as "C"; the contained substance that appears as a peak smaller than the contained substance determined by C and can be identified as a peak and is estimated to be a trace amount is determined as "D".
[0210] [Table 2]
[0211]
[0212] [Table 3]
[0213] (Table 3)
[0214] serial number <![CDATA[KBH4]]> <![CDATA[K 0.67 Al6O 9.33 ]]> <![CDATA[K3AlF6]]> <![CDATA[KBO2]]> Al <![CDATA[Al(OH)3]]> Test Example 24 B B B A A - Test Example 25 - A B - A B
[0215] [Test Example 1]
[0216] Test Example 1 is a comparative example.
[0217] As shown in Table 1, as raw materials, 6.98 g of sodium metaborate (NaBO2) powder, 8.01 g of sodium tetraborate (Na2B4O7) powder, 2.17 g of sodium fluoride powder (NaF) and 11.45 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 1 is 0.89. As a reaction process, the closed container is heated to 510°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.75 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.6 MPa. No cleaning process was performed in Test Example 1. Through the above process, the product involved in Test Example 1 was obtained.
[0218] Fig.15 : is a diagram showing an X-ray diffraction pattern of the product involved in Test Example 1. In Test Example 1, iota-alumina (Na 0.67 Al6O 9.33 ) as the main component of the product. As shown in Table 2 and Fig.15As shown, iota-alumina (Na 0.67 Al6O 9.33 ), sodium borohydride (NaBH4), sodium metaborate (NaBO2) and aluminum (Al), sodium hexafluoroaluminate (Na3AlF6) and sodium tetraborate (Na2B4O7) were detected as AlB2C determination components, and aluminum diboride (AlB2) was detected as D determination component.
[0219] The results of Test Example 1 show that iota-alumina can be produced even when the Na / B ratio is 0.89. On the other hand, since the cleaning step was not performed in Test Example 1, it is considered that sodium borohydride (NaBH4) was not removed.
[0220] [Test Example 2]
[0221] Test Example 2 is an embodiment.
[0222] As shown in Table 1, as raw materials, 1.95 g of sodium metaborate (NaBO2) powder, 0.05 g of potassium fluoride (KF) powder and 1.06 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 2 is 1.03. As a reaction process, the closed container is heated to 569°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.90 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.51 MPa. In Test Example 2, as a cleaning process, cleaning is performed using pure water at high temperature. Through the above process, the product involved in Test Example 2 is obtained.
[0223] In Experimental Example 2, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, iota-alumina (Na 2 O 2 ) was detected as the A determination component from the product involved in Test Example 2. 0.67 Al6O 9.33 ) and aluminum (Al).
[0224] The results of Test Example 2 show that iota-alumina can be produced even when potassium fluoride (KF) is used as the fluoride as the raw material.
[0225] [Test Example 3]
[0226] Test Example 3 is a comparative example.
[0227] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 1.44 g of aluminum fluoride (AlF3) powder and 11.45 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 3 is 1.00. As a reaction process, the closed container is heated to 510°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.75 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.56 MPa. No cleaning process was performed in Test Example 3. Through the above process, the product involved in Test Example 3 was obtained.
[0228] Fig.16 : is a diagram showing an X-ray diffraction pattern of a product involved in Test Example 3. In Test Example 3, iota-alumina (Na 0.67 Al6O 9.33 ) as the main component of the product. As shown in Table 2 and Fig.16 As shown, sodium borohydride (NaBH4), iota-alumina (Na 0.67 Al6O 9.33 ) and aluminum (Al), sodium metaborate (NaBO2) was detected as the B determination component, and sodium hexafluoroaluminate (Na3AlF6) was detected as the C determination component.
[0229] According to the results of Test Example 3, even when aluminum fluoride (AlF3) is used as the fluoride as the raw material, iota-alumina can be generated. On the other hand, since the cleaning process is not performed in Test Example 3, it can be considered that sodium borohydride (NaBH4) and sodium metaborate (NaBO2) are not removed.
[0230] [Test Example 4]
[0231] Test Example 4 is an embodiment.
[0232] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 1.81 g of sodium hexafluoroaluminate (Na3AlF6) and 11.45 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 4 is 1.10. As a reaction process, the closed container is heated to 510°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.75 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.54 MPa. In Test Example 4, as a cleaning process, diethylene glycol dimethyl ether is used for cleaning. Through the above process, the product involved in Test Example 4 is obtained.
[0233] Fig.17: is a diagram showing an X-ray diffraction pattern of a product involved in Test Example 4. In Test Example 4, iota-alumina (Na 0.67 Al6O 9.33 ) as the main component of the product. As shown in Table 2 and Fig.17 As shown, iota-alumina (Na 0.67 Al6O 9.33 ), aluminum (Al) and sodium metaborate (NaBO2) were detected as B determination components, and sodium hexafluoroaluminate (Na3AlF6) was detected as C determination component.
[0234] The results of Test Example 4 show that iota-alumina can also be generated when sodium hexafluoroaluminate (Na3AlF6) is used as the fluoride as the raw material.
[0235] [Test Example 5]
[0236] Test Example 5 is an embodiment.
[0237] As shown in Table 1, as raw materials, 1.48 g of sodium tetraborate (Na2B4O7) powder, 0.83 g of sodium fluoride (NaF) and 1.27 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 5 is 1.17. As a reaction process, the closed container is heated to 500°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.86 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.63 MPa. In Test Example 5, as a cleaning process, diethylene glycol dimethyl ether is used for cleaning. Through the above process, the product involved in Test Example 5 is obtained.
[0238] In Experimental Example 5, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, iota-alumina (Na 0.67 Al6O 9.33 ), aluminum (Al) was detected as the B determination component.
[0239] The results of Test Example 5 show that iota-alumina can be generated even when sodium tetraborate (Na2B4O7) is used as the alkali metal compound as the raw material.
[0240] [Test Example 6]
[0241] Test Example 6 is a comparative example.
[0242] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 2.17 g of sodium fluoride (NaF) and 11.45 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 6 is 1.19. As a reaction process, the closed container is heated to 490°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.75 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.64 MPa. No cleaning process was performed in Test Example 6. Through the above process, the product involved in Test Example 6 was obtained.
[0243] Fig.18 : is a diagram showing an X-ray diffraction pattern of the product involved in Test Example 6. In Test Example 6, iota-alumina (Na 0.67 Al6O 9.33 ) as the main component of the product. As shown in Table 2 and Fig.18 As shown, sodium borohydride (NaBH4) and iotalumina (Na 0.67 Al6O 9.33 ), aluminum (Al) and sodium metaborate (NaBO2) were detected as B determination components, and sodium hexafluoroaluminate (Na3AlF6) was detected as C determination component.
[0244] The results of Test Example 6 show that iota-alumina can be removed even when the heating temperature is set to 490° C. On the other hand, since the cleaning step is not performed in Test Example 6, it is considered that sodium borohydride (NaBH 4 ) and sodium metaborate (NaBO 2 ) are not removed.
[0245] [Test Example 7]
[0246] Test Example 7 is an embodiment.
[0247] As shown in Table 1, the product of Test Example 7 was obtained by washing the product of Test Example 6 with pure water at a high temperature of 80° C. to 100° C. for 1 hour as a washing step.
[0248] Fig.19 : is a diagram showing an X-ray diffraction pattern of a product involved in Test Example 7. In Test Example 7, iota-alumina (Na 0.67 Al6O 9.33 ) as the main component of the product. As shown in Table 2 and Fig.19 As shown, iota-alumina (Na 0.67 Al6O 9.33), sodium hexafluoroaluminate (Na3AlF6) was detected as the C component, and aluminum (Al) was detected as the D component. The X-ray diffraction pattern of Test Example 7 is similar to that of iota-alumina (Na 0.67 Al6O 9.33 The data of PDF (registered trademark) (Powder Diffraction File) No. 01-070-7114 of ), indicating that the crystals have no defects.
[0249] In addition, the results of semi-quantitative analysis of the X-ray diffraction spectrum based on the XRD Rietveld method showed that the product contained 95% by mass of iota-alumina, 5% by mass of sodium hexafluoroaluminate, and less than 1% by mass of aluminum (Al). In addition, the specific surface area of the product calculated by the BET (Brunauer-Emmett-Teller) method was 54 m 2 g -1 .
[0250] According to the results of Test Example 7, sodium borohydride (NaBH 4 ) and sodium metaborate (NaBO 2 ) can be removed by washing with pure water.
[0251] In addition, the product involved in Test Example 7 was observed using SEM. As a result, 80 iota-alumina crystals were selected from the imaging range, and the average aspect ratio of the iota-alumina crystals was calculated to be 10.8.
[0252] [Test Example 8]
[0253] Test Example 8 is a comparative example.
[0254] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 0.31 g of sodium hydroxide (NaOH), 1.86 g of sodium fluoride (NaF) and 11.45 g of aluminum (Al) powder were used. In Test Example 8, sodium hydroxide (NaOH) and aluminum (Al) powder were friction mixed, reacted at 240°C for 1 hour, and then the resulting mixture, sodium metaborate (NaBO2) powder and sodium fluoride (NaF) were placed in a closed container with a stirring unit. Here, the Na / B ratio of Test Example 8 is 1.20. As a reaction process, the closed container is heated to 530°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.75 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.65 MPa. No cleaning process was performed in Test Example 8. Through the above process, the product involved in Test Example 8 was obtained.
[0255] Fig. 20 : is a diagram showing an X-ray diffraction pattern of a product involved in Test Example 8. In Test Example 8, iota-alumina (Na 0.67Al6O 9.33 ) as the main component of the product. As shown in Table 2 and Fig. 20 As shown, sodium borohydride (NaBH4) and iotalumina (Na 0.67 Al6O 9.33 ), aluminum (Al) was detected as B determination component, and sodium hexafluoroaluminate (Na3AlF6) and sodium fluoride (NaF) were detected as C determination component.
[0256] The results of Test Example 8 show that iota-alumina can be generated even when dehydration is performed using sodium hydroxide. On the other hand, since the washing step is not performed in Test Example 8, it is considered that sodium borohydride (NaBH4) is not removed.
[0257] [Test Example 9]
[0258] Test Example 9 is an embodiment.
[0259] As shown in Table 1, the product of Test Example 9 was obtained by washing the product of Test Example 8 with diglyme as a washing step.
[0260] In Experimental Example 9, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, iota-alumina (Na 0.67 Al6O 9.33 ) and aluminum (Al), and sodium hexafluoroaluminate (Na3AlF6) and sodium fluoride (NaF) were detected as C determination components.
[0261] The results of Test Example 9 show that sodium borohydride (NaBH 4 ) can be removed by washing with diglyme.
[0262] [Test Example 10]
[0263] Test Example 10 is an embodiment.
[0264] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 0.29 g of sodium hydroxide (NaOH), 1.86 g of sodium fluoride (NaF) and 11.45 g of aluminum (Al) powder were used. In Test Example 10, sodium hydroxide (NaOH) and aluminum (Al) powder were friction mixed, reacted at 240°C for 1 hour, and then the obtained mixture, sodium metaborate (NaBO2) powder and sodium fluoride (NaF) were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 10 is 1.19. As a reaction process, the closed container is heated to 470°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.75 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.69 MPa. In Test Example 10, as a cleaning process, pure water is used for cleaning at high temperature. Through the above process, the product involved in Test Example 10 is obtained.
[0265] In Experimental Example 10, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, aluminum (Al) and iota-alumina (Na2O3) were detected as the A determination component in the product of Test Example 10. 0.67 Al6O 9.33 ), sodium hexafluoroaluminate (Na3AlF6) was detected as B determination component, and aluminum hydroxide was detected as C determination component.
[0266] From the results of Test Example 10, it was found that when the heating temperature was set to 470° C., iota-alumina was produced.
[0267] Here, aluminum hydroxide (Al(OH)3) was detected. It is speculated that this is because the sodium metaborate (NaBO2) remaining in the product dissolved in water during the cleaning process. At a high temperature of nearly 100°C, the alkalinity of water increased and became alkaline, so the unreacted aluminum partially dissolved in water and became aluminum hydroxide.
[0268] [Test Example 11]
[0269] Test Example 11 is an embodiment.
[0270] As shown in Table 1, as raw materials, 5.82g of sodium metaborate (NaBO2) powder, 0.10g of sodium hydroxide (NaOH), 0.62g of sodium fluoride (NaF) and 3.82g of aluminum (Al) powder were used. In Test Example 11, sodium hydroxide (NaOH) and aluminum (Al) powder were friction mixed, reacted at 240°C for 1 hour, and then the obtained mixture, sodium metaborate (NaBO2) powder and sodium fluoride (NaF) were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 11 is 1.20. As a reaction process, the closed container is heated to 560°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.75MPa. The minimum partial pressure of hydrogen in the reaction process is 0.63MPa. In Test Example 11, as a cleaning process, pure water is used for cleaning at high temperature. Through the above process, the product involved in Test Example 11 is obtained.
[0271] In Test Example 11, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method. As a result, 81% by mass of iota-alumina (Na 0.67 Al6O 9.33 ), 7 mass % of aluminum (Al) and 8 mass % of aluminum hydroxide were detected as B determination components, and 2 mass % of sodium hexafluoroaluminate (Na3AlF6) was detected as C determination component.
[0272] From the results of Test Example 11, it was found that when the heating temperature was set to 560° C., iota-alumina was produced.
[0273] Here, aluminum hydroxide (Al(OH)3) was detected. It is speculated that this is because the sodium metaborate (NaBO2) remaining in the product dissolved in water during the cleaning process, and the alkalinity of water increased and became alkaline at a high temperature of nearly 100°C, so the unreacted aluminum partially dissolved in water and became aluminum hydroxide (Al(OH)3).
[0274] [Test Example 12]
[0275] Test Example 12 is an embodiment.
[0276] As shown in Table 1, as raw materials, 1.94 g of sodium metaborate (NaBO2) powder, 0.83 g of sodium fluoride (NaF) and 1.48 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 12 is 1.67. As a reaction process, the closed container is heated to 495°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.89 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.45 MPa. In Test Example 12, as a cleaning process, diethylene glycol dimethyl ether is used for cleaning. Through the above process, the product involved in Test Example 12 is obtained.
[0277] In Experimental Example 12, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, iota-alumina (Na 0.67 Al6O 9.33 ) and aluminum (Al), and sodium hexafluoroaluminate (Na3AlF6) and sodium aluminate (NaAlO2) were detected as B determination components.
[0278] From the results of Test Example 12, it was found that when the heating temperature was set to 495° C., iota-alumina was generated.
[0279] [Test Example 13]
[0280] Test Example 13 is a comparative example.
[0281] As shown in Table 1, as raw materials, 1.94 g of sodium metaborate (NaBO2) powder and 1.28 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, alumina balls (diameter 5 mm) were added as stirring media in the closed container, and the weight ratio of the stirring media to the raw materials was set to 50. Here, the Na / B ratio of Test Example 13 was 1.00. As a reaction process, the closed container was heated to 330°C and hydrogen was introduced, and the stirring unit in the closed container was used to stir while rolling and crushing at a rotation speed of 1150 rpm. The maximum partial pressure of hydrogen in the reaction process was 0.78 MPa. The minimum partial pressure of hydrogen in the reaction process was 0.59 MPa. No cleaning process was performed in Test Example 13. Through the above process, the product involved in Test Example 13 was obtained.
[0282] In Test Example 13, a product containing aluminum (Al) as a main component was obtained. As shown in Table 2, sodium metaborate (NaBO2) and aluminum (Al) were detected as A determination components from the product involved in Test Example 13. ι-alumina (Na 0.67 Al6O 9.33 ).
[0283] In addition, the product of Test Example 13 was subjected to high temperature X-ray diffraction measurement at 600°C in a nitrogen atmosphere. As the A determination component, sodium metaborate (NaBO2) and aluminum (Al) were detected, and as the B determination component, sodium aluminum boric acid (Na2Al2B2O7) was detected. At this time, ι-alumina (Na 0.67 Al6O 9.33 ).
[0284] In Test Example 13, since the temperature in the reaction process was as low as 330°C and rolling and crushing were performed, it is considered that iota-alumina was not generated. In addition, sodium aluminum boric acid (Na2Al2B2O7) was detected in the high-temperature X-ray diffraction measurement of the product involved in Test Example 13 at 600°C in a nitrogen atmosphere. This is considered to be because the non-crystalline sodium aluminum boric acid (Na2Al2B2O7) contained in the product was crystallized due to heating.
[0285] [Test Example 14]
[0286] Test Example 14 is an embodiment.
[0287] As shown in Table 1, the product of Test Example 14 was obtained by washing the product of Test Example 6 with a 2 mass % sodium hydroxide (NaOH) aqueous solution at 80° C. to 100° C. for 1 hour with stirring as a washing step.
[0288] In Test Example 14, a product containing aluminum hydroxide (Al(OH)3) as a main component was obtained. As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method based on the X-ray diffraction spectrum. As a result, the product involved in Test Example 14 contained iota-alumina (Na 0.67 Al6O 9.33 )
[0289] 38 mass %, aluminum hydroxide (Al(OH)3) 62 mass %.
[0290] The results of Test Example 14 showed that when a 2 mass % sodium hydroxide aqueous solution was used as a solvent in the washing step, iota-alumina was produced.
[0291] In Test Example 14, since a 2 mass % sodium hydroxide aqueous solution was used as a solvent in the washing step, iota-alumina (Na 0.67 Al6O 9.33 ) other than the extraction residue dissolved. Here, the generation of aluminum hydroxide (Al(OH)3) is believed to be due to the formation of iota-alumina (Na 0.67 Al6O 9.33) is also partially dissolved together with aluminum (Al) and precipitated in the form of aluminum hydroxide (Al(OH)3).
[0292] Furthermore, the product of Test Example 14 was observed by SEM. As a result, 11 iota-alumina crystals were selected from the imaging range, and the average aspect ratio of the iota-alumina crystals was calculated to be 8.3.
[0293] [Test Example 15]
[0294] Test Example 15 is a comparative example.
[0295] As shown in Table 1, as raw materials, 2.94 g of sodium diborate (Na4B2O5) powder, 0.83 g of sodium fluoride (NaF) and 1.28 g of aluminum (Al) powder were charged into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 15 is 2.65. As a reaction process, the closed container is heated to 495°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.86 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.61 MPa. In Test Example 15, as a cleaning process, diethylene glycol dimethyl ether is used for cleaning. Through the above process, the product involved in Test Example 15 is obtained.
[0296] In Test Example 15, a product containing sodium aluminate (NaAlO2) as a main component was obtained. As shown in Table 2, sodium aluminate (NaAlO2) and sodium fluoride (NaF) were detected as A determination components, and iota-alumina (Na2O3) was detected as B determination component in the product of Test Example 15. 0.67 Al6O 9.33 ) and aluminum (Al).
[0297] In Test Example 15, Na / B is as high as 2.65, so it can be considered that there is an excess of sodium ions in the reaction system, sodium aluminate (NaAlO2) is stably present, and iota-alumina (Na 0.67 Al6O 9.33 ) is not generated sufficiently.
[0298] [Test Example 16]
[0299] Test Example 16 is a comparative example.
[0300] As shown in Table 1, as raw materials, 5.85 g of sodium metaborate (NaBO2) powder and 9.54 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 16 is 1.00. As a reaction process, the closed container is heated to 710°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 1.05 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.89 MPa. In Test Example 16, the temperature in the reaction process is high temperature, so sublimates are produced. Therefore, the substance that is not sublimated and remains in the closed container is regarded as the product involved in Test Example 16. No cleaning process is performed in Test Example 16. Through the above process, the product involved in Test Example 16 is obtained.
[0301] In Test Example 16, a product containing sodium aluminate (NaAlO2) as a main component was obtained. As shown in Table 2, aluminum (Al) was detected as the A determination component, and sodium aluminate (NaAlO2) and iota-alumina (Na2O3) were detected as the B determination components in the product of Test Example 16. 0.67 Al6O 9.33 ).
[0302] In Test Example 16, the temperature in the reaction step was as high as 710° C., so it is considered that a large amount of sodium metaaluminate was generated as an impurity, and the yield of iota-alumina was reduced.
[0303] [Test Example 17]
[0304] Test Example 17 is a comparative example.
[0305] As shown in Table 1, as raw materials, 17.46g of sodium metaborate (NaBO2) powder, 0.28g of sodium hydroxide (NaOH), 1.86g of sodium fluoride (NaF) and 11.45g of aluminum (Al) powder were used. In Test Example 17, sodium hydroxide (NaOH) and aluminum (Al) powder were friction mixed, reacted at 240°C for 1 hour, and then the obtained mixture, sodium metaborate (NaBO2) powder and sodium fluoride (NaF) were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 17 is 1.19. As a reaction process, the closed container is heated to 450°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.76MPa. The minimum partial pressure of hydrogen in the reaction process is 0.69MPa. In Test Example 17, as a cleaning process, pure water is used for cleaning at high temperature. Through the above process, the product involved in Test Example 17 is obtained.
[0306] In Test Example 17, a product containing aluminum (Al) as a main component was obtained. As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method. As a result, 83% by mass of aluminum (Al) was detected as the A determination component of the product involved in Test Example 17, and 8% by mass of iota-alumina (Na2O3) was detected as the B determination component. 0.67 Al6O 9.33 ) and 7 mass % of sodium hexafluoroaluminate (Na3AlF6), and 3 mass % of aluminum hydroxide (Al(OH)3) was detected as the C determination component.
[0307] In Test Example 17, the temperature in the reaction step was as low as 450° C., and thus it is considered that crystallization of iota-alumina was insufficient.
[0308] [Test Example 18]
[0309] Test Example 18 is a comparative example.
[0310] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 2.06 g of sodium hydroxide (NaOH) and 11.45 g of aluminum (Al) powder were mixed and pre-baked at 510°C for 5 hours in a hydrogen atmosphere of 0.35 MPa. The pre-baked mixture was placed in a closed container with a stirring unit. Here, the Na / B ratio of Test Example 18 is 1.19. As a reaction process, the closed container is heated to 510°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.74 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.69 MPa. No cleaning process was performed in Test Example 18. Through the above process, the product involved in Test Example 18 was obtained.
[0311] In Test Example 18, a product containing aluminum (Al) as a main component was obtained. Fig.21 is a diagram showing the X-ray diffraction pattern of the product involved in Test Example 18. As shown in Table 2 and Fig.21 As shown, sodium fluoride (NaF) and aluminum boride (AlB2) were detected as the A judgment component of the product of Test Example 18, and iota-alumina (Na 0.67 Al6O 9.33 ).
[0312] In Test Example 18, fluoride was not added, and although sodium aluminate (NaAlO 2 ) was produced, it is considered that the crystallization of iota-alumina was insufficient.
[0313] [Test Example 19]
[0314] Test Example 19 is an embodiment.
[0315] As shown in Table 1, as raw materials, 19.40g of sodium metaborate (NaBO2) powder, 2.41g of sodium fluoride (NaF) and 10.60g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 19 is 1.19. In addition, the amount of aluminum (Al) powder is 100% relative to the amount of sodium metaborate (NaBO2). As a reaction process, the closed container is heated to 580°C and hydrogen is introduced, and stirred using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.81MPa. The minimum partial pressure of hydrogen in the reaction process is 0.78MPa. In Test Example 19, as a cleaning process, pure water is used for cleaning at high temperature for 60 minutes. Through the above process, the product involved in Test Example 19 is obtained.
[0316] In Experimental Example 19, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method. As a result, 36% by mass of iota-alumina (Na 0.67 Al6O 9.33 ) and 64 mass % of aluminum hydroxide (Al(OH)3).
[0317] The results of Test Example 19 show that iota-alumina can be generated when the heating temperature is set to 580° C. The fact that aluminum (Al) and sodium hexafluoroaluminate (Na3AlF6) were not detected can be inferred to be because sodium metaborate (NaBO2) remaining in the product during the washing process dissolved in water and became alkaline as in Test Example 14.
[0318] [Test Example 20]
[0319] Test Example 20 is an embodiment.
[0320] As shown in Table 1, as raw materials, 19.40 g of sodium metaborate (NaBO2) powder, 2.41 g of sodium fluoride (NaF) and 10.60 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 20 is 1.19. In addition, the amount of aluminum (Al) powder is 100% relative to the amount of sodium metaborate (NaBO2). As a reaction process, the closed container is heated to 610°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.81 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.78 MPa. In Test Example 20, as a cleaning process, pure water is used for cleaning at room temperature of 22°C.
[0321] Through the above steps, the product involved in Test Example 20 was obtained.
[0322] In Test Example 20, a product containing aluminum (Al) as a main component was obtained. As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method. As a result, 59% by mass of aluminum (Al) and 28% by mass of iota-alumina (Na2O3) were detected as the A determination component from the product involved in Test Example 20. 0.67 Al6O 9.33 ), 9 mass % of sodium hexafluoroaluminate (Na3AlF6) was detected as the B determination component, and 5 mass % of aluminum diboride (AlB2) was detected as the C determination component.
[0323] The results of Test Example 20 show that iota-alumina can be generated when the heating temperature is set to 610°C.
[0324] Here, unlike Test Example 19, aluminum hydroxide (Al(OH)3) was not generated. It is speculated that this is because the reaction temperature was as high as 610°C, so the raw material sodium metaborate turned into a neutral oxide containing aluminum during the reaction, and thus the water did not become strongly alkaline during the cleaning process.
[0325] [Test Example 21]
[0326] Test Example 21 is an embodiment.
[0327] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 2.42 g of sodium fluoride (NaF) and 11.45 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 21 is 1.22. As a reaction process, the closed container is heated to 510°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.84 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.78 MPa. In Test Example 21, as a cleaning process, pure water is used for cleaning at a high temperature of 100°C for 60 minutes.
[0328] Through the above steps, the product involved in Test Example 21 was obtained.
[0329] In Test Example 21, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method. As a result, 80% by mass of iota-alumina (Na 0.67 Al6O 9.33 ), 20 mass % of aluminum hydroxide (Al(OH)3) was detected as B determination component.
[0330] The results of Test Example 21 show that iota-alumina can be produced even when the heating temperature is set to 510°C.
[0331] In Test Example 21, during the washing process, water becomes alkaline due to the sodium metaborate (NaBO2) remaining in the product, and aluminum (Al) dissolves at a high temperature of 100°C to form aluminum hydroxide (Al(OH)3), and sodium hexafluoroaluminate (Na3AlF6) also dissolves.
[0332] [Test Example 22]
[0333] Test Example 22 is an embodiment.
[0334] As shown in Table 1, as raw materials, 17.46 g of sodium metaborate (NaBO2) powder, 2.42 g of sodium fluoride (NaF) and 11.45 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 22 is 1.22. As a reaction process, the closed container is heated to 510°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.84 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.78 MPa. In Test Example 22, as a cleaning process, pure water is used for cleaning at room temperature of 25°C for 60 minutes.
[0335] Through the above steps, the product involved in Test Example 22 was obtained.
[0336] In Test Example 22, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method. As a result, 79% by mass of iota-alumina (Na 0.67 Al6O 9.33 ), 16 mass % of aluminum (Al) and 6 mass % of sodium hexafluoroaluminate (Na3AlF6) were detected as B determination components.
[0337] The results of Experimental Example 22 show that even when the temperature of the polar solvent used in the cleaning step is set to room temperature, iota-alumina (Na 0.67 Al6O 9.33 ).
[0338] A Judgment Component
[0339] In Experimental Example 22, it can be considered that in the cleaning process at room temperature, water becomes alkaline due to the dissolution of sodium metaborate (NaBO2) remaining in the product, but because it is at room temperature, the dissolution reaction of aluminum is moderate and the formation of aluminum hydroxide (Al(OH)3) is suppressed.
[0340] [Test Example 23]
[0341] Test Example 23 is an embodiment.
[0342] As shown in Table 1, as raw materials, 17.46g of sodium metaborate (NaBO2) powder, 2.42g of sodium fluoride (NaF) and 11.45g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the Na / B ratio of Test Example 23 is 1.22. As a reaction process, the closed container is heated to 510°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.84MPa. The minimum partial pressure of hydrogen in the reaction process is 0.78MPa. In Test Example 23, as a cleaning process, 50ml of 0.24mol / L (0.875 mass %) hydrochloric acid is used for 60 minutes of cleaning at room temperature. The pH after cleaning is 6.
[0343] Through the above steps, the product involved in Test Example 23 was obtained.
[0344] In Test Example 23, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, a semi-quantitative analysis was performed using the XRD Rietveld method. As a result, 78% by mass of iota-alumina (Na 0.67 Al6O 9.33 ), 17 mass % of aluminum (Al) and 4 mass % of sodium hexafluoroaluminate (Na3AlF6) were detected as B determination components.
[0345] The results of Test Example 23 show that iota-alumina can be removed even if the water in the washing step is acidic.
[0346] In Test Example 23, by washing with 0.24 mol / L hydrochloric acid (HCl) at room temperature, a neutralization reaction occurred with sodium metaborate (NaBO2) remaining in the reaction product, and the pH became 6. Therefore, aluminum was not dissolved in the washing process, and it can be considered that the formation of aluminum hydroxide (Al(OH)3) was suppressed, and sodium hexafluoroaluminate (Na3AlF6) was slightly reduced.
[0347] [Test Example 24]
[0348] Test Example 24 is a comparative example.
[0349] As shown in Table 1, as raw materials, 7.24 g of potassium borate (KBO2) powder, 1.00 g of potassium fluoride (KF) and 3.82 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the K / B ratio of Test Example 24 is 1.19. In addition, the amount of aluminum (Al) powder is 160% relative to the amount of potassium borate (KBO2). In the reaction process, the closed container is heated to 522°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.78 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.68 MPa. No cleaning process was performed in Test Example 24. Through the above process, the product involved in Test Example 24 was obtained.
[0350] Fig. 22 24. The X-ray diffraction pattern of the product of Test Example 24 is shown in FIG. 24. In Test Example 24, a product containing potassium metaborate (KBO2) as a main component was obtained. Fig. 22 As shown, potassium metaborate (KBO2) and aluminum (Al) were detected as the A judgment component of the product of Test Example 24, and iota-alumina (K 0.67 Al6O 9.33 ), potassium borohydride (KBH4) and potassium hexafluoroaluminate (K3AlF6).
[0351] The results of Test Example 24 show that iota-alumina (K) can be produced even when potassium is used instead of sodium as the alkali metal. 0.67 Al6O 9.33 ).
[0352] [Test Example 25]
[0353] Test Example 25 is an embodiment.
[0354] As shown in Table 1, as raw materials, 7.24 g of potassium borate (KBO2) powder, 1.00 g of potassium fluoride (KF) and 3.82 g of aluminum (Al) powder were loaded into a closed container with a stirring unit. Here, the K / B ratio of Test Example 25 is 1.19. In addition, the amount of aluminum (Al) powder is 160% relative to the amount of potassium borate (KBO2). As a reaction process, the closed container is heated to 522°C and hydrogen is introduced, and stirring is performed using a stirring unit in the closed container. The maximum partial pressure of hydrogen in the reaction process is 0.78 MPa. The minimum partial pressure of hydrogen in the reaction process is 0.68 MPa. In Test Example 25, as a cleaning process, cleaning is performed using pure water at room temperature. Through the above process, the product involved in Test Example 25 is obtained.
[0355] In Test Example 25, a molten-alumina-containing 0.67 Al6O 9.33 As shown in Table 2, 35% by mass of aluminum (Al) and 36% by mass of iotalumina (K) were detected as the A determination component in the product of Test Example 25. 0.67 Al6O 9.33 ), 14 mass % of potassium hexafluoroaluminate (K3AlF6) and 15 mass % of aluminum hydroxide (Al(OH)3) were detected as B determination components.
[0356] The results of Test Example 25 show that iota-alumina (K) can be produced even when potassium is used instead of sodium as the alkali metal. 0.67 Al6O 9.33 ).
[0357] Industrial Applicability
[0358] iotalumina (Na 0.67 Al6O 9.33 or K 0.67 Al6O 9.33 ) has not yet been mass-produced, and it is not sold as a reagent as of July 2022. This is because there is no cheap and high-purity production method. According to this method, iota-alumina (Na2O3) is generated from sodium metaaluminate (NaAlO2) by the catalytic action of fluoride ions. 0.67 Al6O 9.33 ) principle, by heating cheap materials such as aluminum, sodium borates, and hydrogen, it can generate needle-shaped (whisker-shaped) iota-alumina (Na) together with valuable material sodium borohydride (NaBH4). 0.67 Al6O 9.33 ). Cheap iota-alumina (Na 0.67 Al6O 9.33 ) can be used as a raw material for the production of β-alumina (βAlumina, β"Alumina). In addition, needle-shaped (whisker-shaped) ι-alumina (Na 0.67 Al6O 9.33 or K 0.67 Al6O 9.33 ) can be made into composite materials to increase the strength of resins and metals.
[0359] Explanation of symbols
[0360] 10A to 10D: sealed container; 12, 12b: container body; 14: cover; 16: heater; 18: O-ring; 20: motor; 22: stirring rod; 22A: stirring bar; 24: first conduit; 26: hydrogen supply valve; 28: exhaust valve; 30: second conduit; 32: pressure gauge; 35: scraper; 36: strip-shaped scraper; 37: wide paddle stirring bar; 51: sodium borate powder; 52: aluminum powder; 54: fluoride powder; 55: sodium hydroxide powder; 101: aluminum particles; 101a: aluminum particle surface; 101b: aluminum oxide film; 101c: ι-alumina (Na 0.67 Al6O 9.33 ); 102: sodium borate (NaBO2); 103: sodium fluoride (NaF); 106: sodium aluminate (NaAlO2); 111: sodium borohydride (NaBH4); 112: sodium hydride (NaH); 113: sodium oxide (Na2O); 115: reactant layer (sodium borohydride (NaBH4) 111, sodium hydride (NaH) 112); 117: reducing substance (presumably low-order aluminum fluoride = AlF 1.5 ).
Claims
1. A method for producing iota-alumina, characterized in that: have: A reaction step of mixing a solid raw material including an alkali metal compound, a fluoride, and at least one material selected from an aluminum compound and aluminum and subjecting the mixture to a heat treatment; and The product generated in the reaction step is placed in a washing step in a polar solvent.
2. The method for producing iota-alumina according to claim 1, wherein: The alkali metal compound is at least one selected from sodium aluminate (NaAlO2), sodium borates, sodium hydride (NaH), sodium borohydride (NaBH4), sodium oxide (Na2O), potassium aluminate (KAlO2), potassium borates, potassium hydride (KH), potassium borohydride (KBH4) and potassium oxide (K2O).
3. The method for producing iota-alumina according to claim 2, wherein: The sodium borates are at least one selected from sodium metaborate (NaBO2), sodium tetraborate (Na2B4O7) and sodium diborate (Na4B2O5).
4. The method for producing iota-alumina according to claim 2, wherein: The potassium borates are at least one selected from potassium metaborate (KBO2), potassium tetraborate (K2B4O7) and potassium diborate (K4B2O5).
5. The method for producing iota-alumina according to claim 1, wherein: The fluoride is at least one selected from sodium fluoride (NaF), sodium hexafluoroaluminate (Na3AlF6), potassium fluoride (KF), potassium fluoroaluminate (KAlF4), potassium hexafluoroaluminate (K3AlF6), aluminum fluoride (AlF3) and lithium fluoride (LiF).
6. The method for producing iota-alumina according to claim 1, wherein: The aluminum compound is at least one selected from the group consisting of sodium aluminate (NaAlO2), potassium aluminate (KAlO2), aluminum oxide (Al2O3) and aluminum fluoride (AlF3).
7. The method for producing iota-alumina according to claim 1, wherein: The polar solvent is water.
8. An iota-alumina, characterized in that The crystal habit is rod-shaped or needle-shaped.
9. iota-alumina according to claim 8, characterized in that The average aspect ratio of the iota-alumina crystals is 3 or more and 30 or less.
Citation Information
Patent Citations
Production of platy iota-alumina
JP1993201723A